Francisco J. Romero Salvadó. ¿Quién mató a Eduardo Dato? Comedia política y tragedia social en España, 1892-1921. Granada, Comares, 2020, 354 páginas - González Flores, Andrés (Hispania Nova, 2021)
Book review